Economic Use of Brewer’s Dried Grain (BDG) in the Diet of Swine - Rijal, T. B.; Nepali, D. B.; Sah, R. A.; Sharma, M. P. (Nepal Journal of Science and Technology, 2010)
An experiment was conducted from 18th October, 2006 to 18th January, 2007 at IAAS Livestock Farm, Rampur, Chitwan to determine the substitution effects of soybean meal with brewer's dried grain (BDG) on the performance, economics and meat traits of swine production. Starter, grower and finisher diets were formulated containing 18, 16, and 14% CP respectively with 3000 Kcal/kg ME and adequately supplemented with required vitamins, minerals and amino acids. The treatments were: diet without brewer's dried grain -T1 (control diet), diet substituted with 10% brewer's dried grain-T2, diet substituted with 20% brewer's dried grain-T3, diet substituted with 30% brewer's dried grain-T4 and diet substituted with 35% brewer's dried grain-T5. Twenty weaned piglets having 7.37 to 7.94 kg live weight were housed in individual pens. Five piglets were randomly assigned to the five treatments following a randomized complete block design (RCBD) considering each individual as a replication. Fortnightly live weight, daily feed consumption, income over feed and pig cost, and different meat traits of pigs were recorded. The effect of replacing formulated diets with various level of brewer's dried grains on body weight gain was significant (p<0.01) with higher level of substitution resulting lower live-weight at the end of each of starter, grower and finisher diet period. The average body weight of piglets substituted with 35%BDG (27.00kg) and 30%BDG (39.75kg) were significantly lower (p<0.01) compared to the weight of piglets receiving 0% (65.75kg), 10% (64.25kg) and 20% (60.25kg) BDG replaced diets at the end of 3 months experimental period. A significant reduction (P<0.01) in average daily feed consumption were also recorded with increasing level of BDG in the diet. Better feed conversion ratio (FCR) was observed in T2 at early period which at finisher stage T3 diet resulted significantly better FCR which was at par with T1 and T2 diet fed group. However, T5 diet resulted the poorest feed conversion ratio of 5.26, 4.92 and 5.87 for starter, grower and finisher respectively. There was reduction in feed cost with different levels of BDG substitution in diet of pig. Highest income (in per cent) over expenditure (109.01%) was found in T2 followed by T1, T3, and T4. Lowest income over expenditure (-8.2%) was found in T5. Highest dressing percent (71.87%) was recorded in T1 and lowest (70%) in T5 diet fed group. Inclusion of 10-20% BDG seems most acceptable level of substitution of SBM. However, this result needs to be verified under farmer's management condition before recommendation. Key words: Brewer's dried grains; Swine performance DOI: 10.3126/njst.v10i0.2820 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 29-35